Political Decentralisation and Local Economic Development: Findings on the pro-poor responsiveness in 5 Cambodian communes - Nico Westphal (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2011)
Decentralisation and local economic development (LED) are two major development strategies that both have an explicit or inexplicit focus on poverty reduction. Political decentralisation offers principally two channels that allow to better orient policies to the needs of the poor, either through electoral processes at the local level or through direct participation. Local economic development is widely based on the assumption that interventions need to be tailored to the specific local characteristics. Governance mechanisms are inherent to both concepts, considering that especially participation is an important element in policy-making. This research project analyses the voice-responsiveness mechanism, which is based on direct citizen participation in a governance-setting rooted in the context of a decentralisation reform. Analysing the Cambodian decentralisation process, this study finds that the legal framework and the resulting participation of poor economic actors gives them significant influence on defining the strategic outline for local economic development policies and that these opportunities are largely exploited by them. Such an inclusive decision-making process leads to policies that largely reflect the poor's needs. Nonetheless, the results show a clear location- and actor-specificity regarding the inclusion and voice of poor people in policy-making and of the resulting LED-policies. It thus supports the argument that political decentralisation can be a driving but not a decisive factor for pro-poor oriented local economic development policies.
Keywords: 330; Cambodia; Decentralization; Economic Development; Dezentralisierung; Kommunale Entwicklung; Armutsbekämpfung; Entwicklung; Kambodscha